Lipofibromatosis-like neural tumor: Case report of a unique infantile presentation - Diana W. Bartenstein, BA; Taylor M. Coe, MD; Samantha C. Gordon, MD; Alison M. Friedmann, MD; Maryanne M. Senna, MD; Cassandra M. Kelleher, MD; Cristina R. Antonescu, MD; Rosalynn M. Nazarian, MD; Elena B. Hawryluk, MD, PhD (Elsevier, 2018)
A 14-month-old boy presented with a slow-growing, asymptomatic back plaque, which was biopsied and found to have S100 positivity, sparse CD34 staining, and no significant mitotic activity, nuclear pleomorphism, or necrosis; genetic workup found LMNA-NTRK1 gene fusion, overall consistent with lipofibromatosis-like neural tumor (LPF-NT). LPF-NT is rare, with 14 cases previously reported, and our patient is the first report of this diagnosis in infancy. This case report and literature review includes comparison of similar diagnoses including lipofibromatosis, low-grade malignant peripheral nerve sheath tumor, infantile fibrosarcoma, and dermatofibrosarcoma protuberans and serves to aid detection of LPF-NT presenting in pediatric patients by highlighting similarities and differences that should prompt consideration. LPF-NT shows locally aggressive behavior only and should not be confused with conditions that have potential for distant spread. However, case reports of metastasizing LMNA-NTRK1 tumors draw into question whether growths with this gene fusion exist on a spectrum of disease severity. Our patient was treated with wide local excision and has developed no complications or evidence of recurrence with 6 months of follow-up time.